Identification of predictors of drug sensitivity using patient-derived models of esophageal squamous cell carcinoma - Dan Su (Nature Portfolio, 2019)
Predicting the drug response of patients with cancer is crucial for implementing targeted therapy. Here, Su et al. make patient-derived cell lines and perform targeted sequencing and RNA-seq to identify CDKN2A/2B loss as a predictor of response to CDK4/6 inhibitors in esophageal squamous cell carcinoma.